(untitled) (Global Journal of Human-Social Science, 2018)
This study analyzes the determinants of foreign direct investment inflow in Tanzania. The paper used the annual time series data which covered the period between 1990-2015. With the help of E-views 7 software, this study used the Ordinary Least Square (OLS) estimation methods to examine the relationship between foreign direct investment inflow and its determinants which were selected in the sample of the study. Unit roots test by using Augmented Dickey Fuller test was also employed in this study to see stationary and non-stationary of the variables that is if the variable has the unit root or not. Data collected from the World Bank Development indicators. Market size, trade openness, inflation rate and exchange rate are among of the selected sample variables in this study. The results found that exchange rate is a major determinant of foreign direct investment inflow into Tanzania and this indicates that the fluctuated exchange rate policy adopted by the country increases the inflow of foreign direct investment in the country. Therefore, the policy makers and responsible authority should continue to adopt effective policy measures so as to attract more foreign investors. The market size was found to be significant but with the negative sign which indicates that the small market size discourages the inflow of foreign direct investment in the country. The government needs to make more effort in the expansion of the market size in order to attract more foreign investors. Trade openness and inflation rate were found to have insignificant relationship with foreign direct investment inflow in the country.